Experiences from a land-based learning project focused on local food interventions - Abbey Palmer; Phillip Warsaw; Aaron McKim; R. Bud McKendree; Maezie Nettleton; Tiffany Marzolino; Haley Brasier (Journal of Agriculture, Food Systems, and Community Development)
Farm-to-school programs have many documented benefits but are typically centered around school gardens or local food procurement, which can be a limitation for schools. Land-based learning takes a student-centric approach to agricultural education, allowing students to identify and develop interventions to improve their local food system based on the content presented in the classroom, providing the possibility for delivering farm-to-school content outside of its traditional settings. We present findings from the evaluation of a land-based learning program implemented in northern Michigan. The program engaged two teachers and their respective students across two schools, each school’s food-service directors, two local farmers, and a Michigan State University extension educator to form two Locally Integrated Food Teams (LIFTs). Students were presented content about local food procurement across 20 instructional sessions, during which each LIFT worked to develop a shared understanding of the local food system and school lunch sourcing to identify an intervention to increase the amount of local food in their school lunches. The LIFTs then proposed their interventions to Michigan State University faculty, implemented their intervention, and presented the results of the intervention during the program wrap-up day. To explore the experiences of LIFT members, we conducted focus groups and collected observational data from the program participants. We find that delivering farm-to-school content in a land-based learning framework provides many of the same benefits of traditional farm-to-school programs, while allowing for greater flexibility in the construction of the program and providing additional educational benefits not commonly discussed in the farm-to-school literature.